1952
DOI: 10.1037/h0059738
|View full text |Cite
|
Sign up to set email alerts
|

A projective measure of need for affiliation.

Abstract: McClelland et al. (S,7) have developed what appears to be a valid method for measuring achievement motivation by means of a content analysis of the Thematic Apperception Test ( 9) or TAT stories. The TAT used here involves the writing of brief imaginative stories in response to certain pictures. Recently there have been attempts to extend the applicability of McClelland's content analysis to other needs. Roby (10) and Birney (3) have developed scoring systems for the need for security.. The problem of finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
1
1

Year Published

1955
1955
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(69 citation statements)
references
References 4 publications
7
60
1
1
Order By: Relevance
“…For example, significant correlations between OMT scores and corresponding TAT scores were found in a Cameroonian subsample but not in other subsamples (German, Costa Rican) of Chasiotis and Hofer's (2003) studies. Supporting the OMT's sensitivity towards motive arousal, Scheffer et al (2007, Study 1) 2 found that the OMT-affiliation score could be predicted in an affiliation motive arousal procedure (as proposed by Shipley and Veroff 1952). The PSE-affiliation score, however, could only be predicted marginally in this study.…”
Section: Three Examples Of Implicit Motive Measurescontrasting
confidence: 45%
“…For example, significant correlations between OMT scores and corresponding TAT scores were found in a Cameroonian subsample but not in other subsamples (German, Costa Rican) of Chasiotis and Hofer's (2003) studies. Supporting the OMT's sensitivity towards motive arousal, Scheffer et al (2007, Study 1) 2 found that the OMT-affiliation score could be predicted in an affiliation motive arousal procedure (as proposed by Shipley and Veroff 1952). The PSE-affiliation score, however, could only be predicted marginally in this study.…”
Section: Three Examples Of Implicit Motive Measurescontrasting
confidence: 45%
“…Although affiliation-intimacy motivation is generally linked with warm, friendly actions, there is also a small but consistent set of findings linking affiliation motivation with defensiveness and "prickliness" in the face of threat (Byrne, 1961;Terhune, 1968). i A scoring system for intimacy motivation was developed by McAdams (1980) to improve on the affdiation-motivation scoring systems developed by Veroff and others (Atldnson, Heyns, & Veroff, 1954;Shipley & Veroff, 1952). Although there are both theoretical and empirical differences between intimacy and affiliation motives, the scoring system used for the present study incorporates elements of both systems (and hence is referred to as affiliation-intimacy).…”
mentioning
confidence: 99%
“…Social awareness Shipley and Veroff (1952) Learning requires a social context to be effective Social context Hearn and Scott (1998) Technology in the distance environment must be able to address the social context of learning …”
Section: Background: Distance Education and Prior Researchmentioning
confidence: 99%